2019
DOI: 10.1002/mpr.1785
|View full text |Cite
|
Sign up to set email alerts
|

Testing for response shift in treatment evaluation of change in self‐reported psychopathology amongst secondary psychiatric care outpatients

Abstract: ObjectivesIf patients change their perspective due to treatment, this may alter the way they conceptualize, prioritize, or calibrate questionnaire items. These psychological changes, also called “response shifts,” may pose a threat to the measurement of therapeutic change in patients. Therefore, it is important to test the occurrence of response shift in patients across their treatment.MethodsThis study focused on self‐reported psychological distress/psychopathology in a naturalistic sample of 206 psychiatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 86 publications
1
23
0
Order By: Relevance
“…The detected response shift was not found to be associated with diabetes distress, and only marginally increased overall treatment effectiveness. Occurrence of response shift in measures of depression has been evidenced in previous studies too [10][11][12][13]41]. Similar to our findings, some studies indicated response shift in measures like depressive affect, where Carlier [13] detected reconceptualization of mood items, Smith et al [12] found reprioritization of the item 'how often do you feel depressed', and Wu [11] found considerable recalibration response shift in items of the negative attitude factor.…”
Section: Interpretation and Explanation Of Response Shiftsupporting
confidence: 91%
See 1 more Smart Citation
“…The detected response shift was not found to be associated with diabetes distress, and only marginally increased overall treatment effectiveness. Occurrence of response shift in measures of depression has been evidenced in previous studies too [10][11][12][13]41]. Similar to our findings, some studies indicated response shift in measures like depressive affect, where Carlier [13] detected reconceptualization of mood items, Smith et al [12] found reprioritization of the item 'how often do you feel depressed', and Wu [11] found considerable recalibration response shift in items of the negative attitude factor.…”
Section: Interpretation and Explanation Of Response Shiftsupporting
confidence: 91%
“…Finally, Carlier at al. [ 13 ] investigated response shift in self-reported psychological distress from psychiatric outpatients who received psychotherapy (mainly CBT), pharmacotherapy, or a combination of both. They found several indications of reprioritization and reconceptualization, but these response shifts did not impact the assessment of treatment effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…SOS-6 was established as a factor with six observable variables between errors. The Weighted Least Squares Means and Variance Adjusted (WLSMV; Beauducel & Herzberg, 2006 ; Carlier et al, 2019 ; Hirschfeld & von Brachel, 2014 ) estimation method was used; the WLSMV estimation method is a robust estimator in the absence of multivariate normality and is designed for ordinal data ( Hu & Bentler, 2016 ). The following criteria were taken into account to evaluate the multigroup CFA: CFI and TLI> .90 and RMSEA <.08 ( Hu & Bentler, 1999 ; Manrique & Semenova, 2015 ; Wang & Wang, 2012 ), as well as the difference between the CFI comparative index values ( Bentler, 1990 ).…”
Section: Studymentioning
confidence: 99%
“…Severe; not measuring same construct Carlier et al (2019) found in a sample of individuals receiving outpatient psychiatric treatment (multiple diagnoses) that items assessing suicidal ideation and hopelessness broke apart from the mood subscale to form a distinct factor, which was different from the structure of the items at pretreatment. The authors concluded that these concepts became more distinct after treatment, whereas the other mood-related items did not.…”
Section: Configural Invariancementioning
confidence: 91%
“…Furthermore, Sprangers and Schwartz (1999) defined catalysts as changes in health status (e.g., an intervention, elapsed time, a diagnosis, or medical procedure) and mechanisms as behavioral, cognitive, and affective processes that accommodate the catalyst (e.g., coping or social comparison) but are unrelated to true change in construct. Their theoretical model of response shift proposes that a catalyst triggers may not be measuring same construct Carlier et al (2019) found response shift in a sample of individuals receiving outpatient treatment in two items-one cognitive ("I could not concentrate well") and one somatic ("I was shaking or trembling") such that the factor loadings were higher after treatment than before. The authors concluded that the patients placed more value on these problems at posttreatment.…”
Section: Statistical Mediation Analysismentioning
confidence: 99%